»There’s nothing worse than athletes«: criticism of athletics and professionalism in the archaic and classical periods - Edmund, Stewart (Weidmannsche Verlagsbuchhandlung GmbH, 2014)
Victory in the great athletic games was widely seen in the Greek world as one of the summits of human achievement. Yet a surprisingly large number of texts present a negative view of athletics, including Xenophanes fr. 2 West and Euripides fr. 282 TrGF. The reasons for this criticism – which has variously been interpreted as a critique of the aristocracy, professionalism in sport or the reaction of a minority of intellectuals – remain obscure. This paper argues that opposition to athletics was not political but part of a longstanding debate on the relative merits of different forms of skill (τέχνη). This debate was prompted by widespread economic specialisation and professionalism in the fields of athletics, poetry and philosophy (among others). The criticism of athletics be-comes part of a strategy, by which the professional promotes his own form of τέχνη, with the implicit aim of winning respect and financial rewards. Professionals operated in a market for knowledge, one in which they had to sell their skills, justify their fees and counter common prejudices against paid work. Our texts reflect the tendency for professionals to achieve these aims by launching pre-emptive attacks upon their competitors. Athletes became a common target for such invective because their unwavering popularity and success at eliciting rewards in the archaic and classical periods made them a constant target of envy from other professionals.